Increasing Public Satisfaction and Trust Based on a Islamic Service Quality Perspective at the North Buton Regency PTSP Service - yusuf, Hayat (Jurnal Ilmiah Ekonomi Islam, 2024)
Disclosure of information, when linked to service activities, helps encourage people to become more aware of their rights and obligations. Therefore, the hope to be able to get the best service is now also starting to depend on government organizations. The research objective is to analyze the effect of service quality on satisfaction and public trust. This research is explanatory. The research location is the North Buton Regency Investment and One-Stop Integrated Services (PTSP) Service with a target population of 149 people processing permits. The measurement was carried out using a Likert scale (Summated Scale) with five categories on a scale of 1 to 5, namely: (1) strongly disagree, (2) disagree, (3) neutral, (4) agree, (5) strongly agree. The analysis used to answer the hypothesis in this research uses a Structural Equation Model (SEM) using the AMOS 26 program package. There is a positive and significant influence between service quality on satisfaction with a beta coefficient of 0.903 and a probability of 0.000. There is a positive and significant effect of service quality on trust with a beta coefficient of 0.572 and a probability of 0.004. There is a positive and significant influence between satisfaction on trust with a beta coefficient of 0.369 and a probability of 0.044. There is a positive influence between service quality on trust which is mediated by satisfaction. The nature of this mediation is partial mediation with a beta coefficient of 0.517. the better the service quality, the satisfaction will increase. The better the service quality, the more trust will increase. The higher the satisfaction felt, the greater the trust. Service quality can indirectly influence trust through satisfaction.